(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In this article, higher education is the main support and foundation of society. In addition, extensive foreign experience in improving the education system and quality has been studied. As a result of these analyses, proposals and recommendations for improving the education system of the Republic of Uzbekistan were developed.